ANGI-11. RAB27 IS REQUIRED FOR REGULATING INTACT VASCULATURE IN GLIOBLASTOMA. (14th November 2022) - Adnani, Lata; Meehan, Brian; Rak, Janusz
Abstract: Rab27 is a GTPase involved in the biogenesis of extracellular vesicles (EVs) and cellular secretion pathway. Among two Rab27 isoforms (a and b) Rab27a has been identified in regulating angiogenesis during development and wound healing via VEGFR1. Here, we show that Rab27 plays a role in the development and stability of the brain vasculature including pathological angiogenesis in glioblastoma.. Thus, relative to wild-type C57bl/6 (WT) and double heterozygous Rab27a +/- ;Rab27b +/- (dHET) mice, animals with Rab27a/b double knock-out (Rab27a/b-dKO) exhibit reduced microvascular density in brain cortices. Additionally, we also observed a reduction in permeability of Evans Blue in the Rab27 dKO cortices relative to controls. When neoangiogensis was induced following orthotopic inoculation of mouse glioma cells (GL261), a similar reduction and morphological anomalies were observed in the tumour vasculature relative to tumours established in control mice. Moreover, vascular permeability of tumours in Rab27a/b-dKO mice markedly exceeded that of similar tumours in wild type or heterozygous controls. Our results suggest Rab27a and Rab27b may play a critical role in ensuring stability of the vasculature under physiological conditions and in glioma.